INDIGENOUS FORESTS AND CARBON TRADING: ASSESSING THE POTENTIAL FOR HUMAN RIGHTS VIOLATIONS - Rangkuti, Liza Hafidzah Yusuf; Batubara, Dinda Aprilia; Syam, Farhans Mahendra (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2024)
To promote national economic growth, the Indonesian government has introduced several laws, including investment policies related to carbon trading in indigenous forests. This article explores the legal concerns surrounding how investment strategies involving carbon trading in these forests could potentially lead to human rights violations, especially affecting Indigenous Peoples (IP). This study utilizes normative research methods and a case approach, with data collected through library research. This study shows that indigenous peoples gain both economically and environmentally from investment strategies involving carbon trading in indigenous forests. However, it may result human rights violations against IP. The state's failure to fully recognize Indigenous Peoples's rights has delayed the official acknowledgment of Indigenous Territories and Indigenous Forests. In contrast, business licenses for companies in the forestry sector trading carbon in Indonesia are processed quickly. This discrepancy can lead to potential human rights violations against IP, including threats to their indigenous forests and unfair access to social forestry management licenses.